Akibat Hukum Lewatnya Batas Waktu Kewajiban Mendaftarkan Akta Pemberian Hak Tanggungan (APHT) Oleh PPAT - Jaenudin Umar (Jurnal Indonesia Sosial Sains, 2021)
The purpose of this research is to find out, understand and analyze whether the delay in registering APHT affects the validity of the Mortgage Rights and to find out, understand and analyze the legal consequences of the passing of the deadline for registering APHT by the PPAT. After researching with the statutory approach and the opinions of scholars, it was concluded that the delay in registering APHT did not affect the validity of the APHT, so that after the APHT was registered it did not affect the birth process of the Mortgage and the validity of the Mortgage Rights, the new Mortgage would be born after 7 (seven). ) the day the APHT is registered completely along with the documents needed for registration, as evidenced by the issuance of a Certificate of Mortgage. Delay in registration will only delay the birth of the Mortgage Rights, but will not affect the validity of the APHT for the Mortgage Registration process. The legal consequence of the passing of the time limit for the obligation to register APHT by PPAT can result in a lawsuit and sanctions against the PPAT itself, both civil and administrative, and can cause losses to the parties who agree, especially creditors.